87 Residual Ischaemia Post Acute Coronary Syndrome (ACS) – Does Revascularisation Improve Prognosis?. (3rd June 2016) - Sekhri, Neha; Fung, Kenneth; Iqbal, Mohammed H; Anwar, Mohammed O; Jones, Daniel A; Mathur, Anthony; Wragg, Andrew; Timmis, Adam
Abstract : Background: Residual myocardial ischaemia early after acute coronary syndromes (ACS) is commonly regarded as an adverse prognostic sign and an indication for revascularisation. However, the benefits of revascularisation for improving prognosis are not known. Methods: Analysis of 597 consecutive patients with ACS treated with coronary stenting, all of whom underwent adenosine stress cardiac magnetic resonance (CMR) perfusion imaging to guide revascularisation decisions. Follow-up data were obtained from hospital electronic health records. Results: The 597 patients (age 59 ± 12 years, 20% female) underwent stress CMR scan, at median of 93 days (IQR: 41, 224 days) after coronary stenting with follow-up for 1.4 years (IQR: 0.6-2.7). Inducible perfusion defects were identified in 293 (49%) patients of whom 18 (6%) died during follow-up compared with 6 (2.0%) patients with no perfusion defects (p=0.01). Of the 293 patients with perfusion defects (Table 1 ), 70 (24%) were revascularised (PCI 54, CABG 26) of whom 5 (7%) died during follow-up compared with 13 (6%) who were not evascularised (p=0.66). K-M survival analysis confirmed that revascularisation was unassociated with survival benefit, regardless of the severity of ischaemia (Figure 1 ). Conclusion: In our patients with ACS and coronary stenting, inducible ischaemia was associated with increased risk of death during follow-up. Revascularisation did not appear to reduce the risk and should be reserved for improving symptoms in patients on optimal medical therapy.